Statistical yearbook - United Nations Educational, Scientific and Cultural Organization; United Nations Educational, Scientific and Cultural Organization ([Paris Unesco], 1963)
"Reference tables, education, science and technology, and culture and communication."
Annual
Text in English and French.
Keywords: Intellectual life -- Statistics -- Periodicals; Literacy -- Statistics -- Periodicals